SYSTEM - SHIRAKAWA SHINJI (2025)
To provide systems.SOLUTION: A system includes the means of: generating barrier-free information, letting an image or video of a facility be an input; generating a Web page based on the generated barrier-free information; and posting the generated Web page on a homepage of a facility.SELECTED DRAWING: Figure 1 【課題】システムを提供する。【解決手段】施設の画像や動画を入力とし、バリアフリー情報を生成する手段と、生成されたバリアフリー情報を基にＷｅｂページを生成する手段と、生成されたＷｅｂページを施設のホームページに掲載する手段を含むシステム。【選択図】図１